2004
DOI: 10.1097/01.prs.0000131868.67896.83
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fast-Setting Hydroxyapatite Cement for Secondary Craniofacial Contouring

Abstract: Patients who have previously had surgical correction of major craniofacial deformities will often have residual contour deformities they wish to have improved at a later date. The development of hydroxyapatite cement has simplified these procedures. The setting time is reduced to 5 to 8 minutes by mixing the cement with a phosphate-based solution, increasing the tensile strength, and maintaining the same biocompatibility and osseoconductivity. This study includes 48 patients who presented with a variety of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Magee and colleagues described 48 postoperative patients who presented with hollowed temporal areas, frontal asymmetry or recession, and other contour deformities. 16 The cause of the temporal deformity that follows fronto-orbital advancement is controversial. Several studies have implicated the temporal fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…Magee and colleagues described 48 postoperative patients who presented with hollowed temporal areas, frontal asymmetry or recession, and other contour deformities. 16 The cause of the temporal deformity that follows fronto-orbital advancement is controversial. Several studies have implicated the temporal fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found lower complication rates, with the proper selection of patients and placement, on the order of 5-14% [7][8][9]. Verret et al [10] performed one of the largest reviews of 102 patients undergoing craniofacial reconstruction using bone cement.…”
Section: Current Bone Substitutes and Scaffoldsmentioning
confidence: 97%
“…In addition to the hydrolysis reaction of α‐TCP, calcite and monetite are known to react towards apatite, thereby providing an additional source for precipitation of nanosized apatite crystals 6. However, the slow degradation rate with limited bone ingrowth at osseous sites is the major disadvantage of the cement 7, 8. Recently, our group showed that α‐TCP‐based cement (85% α‐TCP, 10% CaHPO 4 , 5% pHA) containing polymeric microspheres were hardly degradable upon implantation in cranial defects in rats and femoral condylar defects in rabbits even after 12 weeks of implantation 8, 9…”
Section: Introductionmentioning
confidence: 99%